Blood, bullets, and bones : the story of forensic science from Sherlock Holmes to DNA - Heos, Bridget (Balzer + Bray, an imprint of HarpercollinsPublishers, 2016)
"Blood, Bullets, and Bones provides young readers with a fresh and fascinating look at the ever-evolving science of forensics. Since the introduction of DNA testing, forensic science has been in the forefront of the public's imagination, thanks especially to popular television shows like CSI: Crime Scene Investigation. But forensic analysis has been practiced for thousands of years. Ancient Chinese detectives studied dead bodies for signs of foul play, and in Victorian England, officials used crime scene photography and criminal profiling to investigate the Jack the Ripper murders. In the intervening decades, forensic science has evolved to use the most cutting-edge, innovative techniques and technologies. In this book, acclaimed author Bridget Heos uses real-life cases to tell the history of modern forensic science, from the first test for arsenic poisoning to fingerprinting, firearm and blood spatter analysis, DNA evidence, and all the important milestones in between. By turns captivating and shocking, Blood, Bullets, and Bones demonstrates the essential role forensic science has played in our criminal justice system"--